STRATEGI KOMUNIKASI INTERPERSONAL DAN KONSELING SFBT DALAM MENGATASI PROKRASTINASI AKADEMIK MAHASISWA BERBASIS PESANTREN - Moch. Nuril Anwar; Hanik Mufaridah (Fakultas Dakwah dan Ushuluddin Universitas Ibrahimy, 2026)
This study aims to examine the psychological, academic, and social barriers that trigger final project procrastination among students of the Islamic Communication and Broadcasting (KPI) Study Program at Ibrahimy University. As an institution integrated with the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School, students carry a dual burden encompassing university academic demands and the standardization of Islamic boarding school competencies. This study employs a qualitative method with a descriptive case study design. The research subjects involved four final-year students who experienced a delay in completing their thesis for one to three years. The results indicated that the root causes of procrastination include cognitive overload due to confusion regarding supervisors' revisions, role conflict resulting from high off-campus organizational activities, and psychological barriers caused by failing the Quran reading competency exam. These conditions triggered students' withdrawal from the academic environment. This study concludes that the synergy of dialogic-humanistic interpersonal communication from supervisors and the head of the study program, along with the implementation of Solution-Focused Brief Therapy (SFBT) counseling interventions, has proven effective. This approach successfully reduced anxiety, unraveled students' obstacles into concrete action steps, and restored their focus on completing their final projects.